A MODEL OF GROUP GUIDANCE TO ENHANCE STUDENT RESILIENCE IN THE COVID-19 ERA - Siti Aminah, Laila; Arifin, Wahyu Eko; Dja'far, Veri Hardinansyah (Transpublika Publisher, 2021)
This research aims to analyze group guidance model to enhance student resilience in the covid-19 era. This study employs a literature review is the method, by sifting through research publications published between 2015-2021. The majority of the publications were from national and international journals of guidance and counseling, psychology, and education. Using the keywords